Inflammatory bowel disease: Medical management - Al-Gindan Yusuf (The Saudi Journal of Gastroenterology, 1995)
Various papers have been published on inflammatory bowel disease in the Kingdom of Saudi Arabia and other Gulf States during last decade. Apparently, the published data contradict previous belief and indi-cate that, we might deal here with a medical problem. However, data on the magnitude of this disease in our community remains uncertain. Could we attribute this possible change to the improvement in diag-nostic procedure or to the change in life style? Unfortunately, the literature does not provide us with a convicting answer to this question yet. However, at this stage a review of the medical management in inflammatory bowel disease seems to be justified. Hence currently used drugs in the management in inflammatory bowel disease are reviewed in this paper. Some of the potentially effective drugs for the future are also summarized.